PENGARUH DIMENSI KUALITAS PELAYANAN ORGANISASI TERHADAP KEPUASAN KONSUMEN (STUDI PADA STIE TOTALWIN SEMARANG) - Mulyanto, Kukuh (STIE Totalwin Semarang, 2012)
Purpose of this study was to examine service quality toward studentâs satisfaction. The population of this research is the student of STIE Totalwin Semarang. The result of this research indicates that service qualityâs factor has a significant influence toward the studentâs satisfaction. Keywords: service quality, satisfaction